Physiologic effects of chaning rifle carrying position in elite biathletes - Livingood, E.; Burgess, I.; Marshall, G.; Becker, J. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Skiing while carrying the additional mass of a rifle has detrimental effects on both physiologic and biomechanical measures of skiing performance [1,2]. However, it may be possible to offset these detrimental impacts by manipulating the position of the rifle on the athlete`s back or the tightness of the harness. While this has been considered in theoretical studies [3], to date it has not been investigated experimentally. Therefore, the primary purpose of this study was to evaluate the impact of changing rifle position and harness tightness on physiologic response during skiing in elite biathletes. Secondarily, we also examined whether harness position and tightness influences shooting timing.